Subhash Chandra Bose: his life & times - Gupta, Hemendranath Das (Gurugram Teacher's press, 2022)
Subhas Chandra Bose, widely known throughout India as Netaji, was an Indian nationalist and prominent figure of the Indian independence movement, whose attempt during World War II to rid India of British rule with the help of Nazi Germany and Japan left a troubled legacy.[4][5][6] Bose was a twice-elected President of the Indian National Congress, founder and President of the All India Forward Bloc and founder and Head of State of the Provisional Government of Free India, which he led alongside the Indian National Army from 1943 until his death in 1945. Bose is perhaps best known for his advocacy and leadership of an armed struggle for Indian independence against the British Empire, as well as his early calls for Purna Swaraj or complete self-rule, for the people of India. The human inquisitiveness is so wide that it would take centuries to explore the facts of the world. However, this series tries to achieve the impossible by presenting you almost all you ever wanted to know. The reader can surf through the collection and gather all information about famed personalities, countries, languages, professions, computers, health and fitness, sports, quotations, world, traveling destinations, musical instruments, hobbies, spiritual teachings, health disorders, history, etc.
Keywords: Biography